Improving Students' Writing Skill in Recount Text by Using Picture Series Medium - Lyza Yustika (Universitas Maritim Raja Ali Haji (UMRAH), 2021)
This research aimed to describe how picture series medium can increase the students’s writing skill for eighth grade at state junior high school 1 of Bintan. Classroom action research was the research design. The research comprised of two cycles with four meeting in the two cycles. A test was the main data of this research. Twenty students in VIII B at state junior high school 1 of Bintan, in the academic year of 019/2020 was the subject of this research. The outcome appeared there were upgrades in students’ writing skill. It tends to be seen from the outcome of each post-test in the two cycles. Students’ test average in cycle 1 was 63.57. Students’ test average in second cycle was 68.87. It means picture series medium could help students in improving their writing skill.